RESPECT FOR PEOPLE: THE FORGOTTEN PRINCIPLE IN LEAN MANUFACTURING IMPLEMENTATION - Nicolas Cardon; Francisco Bribiescas (European Scientific Journal, ESJ, 2015)
Nowadays companies live in a constant changing world where customers demand better products, higher quality and shorter delivery times. To achieve these customers requirements companies look for strategies, methodologies and/or philosophies that may help them to increase their productivity, and Lean Manufacturing (or Toyota Production System) has been one of the most popular in the last decades. But in the eagerness of being more productive managers mainly focus on the technical part of Lean and forget about the second and equally important principle “Respect for People”. In this paper this “Respect for the People “principle is discussed, and its meaning is explained based on the explanation of several experts in the field. At the end, a small field research (based in semi-structure interviews) of the topic is explained. The present paper is a qualitative research with the purpose to explore and get a deep knowledge about the “Respect for People”, and how department managers perceive and work this principle in their job.